Copper‐Catalyzed Oxidative Benzylic C(sp3)−H Cyclization for the Synthesis of β‐Lactams. Issue 20 (18th March 2020) - Nozawa‐Kumada, Kanako; Saga, Satoshi; Matsuzawa, Yuta; Hayashi, Masahito; Shigeno, Masanori; Kondo, Yoshinori
Abstract: β‐Lactams are important structural motifs because of their ubiquity in natural products and pharmaceuticals. We report herein a Cu‐catalyzed intramolecular oxidative C(sp 3 )−H amidation for the synthesis of β‐lactams using t BuOO t Bu. This method is based on Kharasch–Sosnovsky amidation and does not require prefunctionalization of C(sp 3 )−H bonds or the installation of a directing group, thereby allowing for the straightforward synthesis of β‐lactams. Our intramolecular functionalization protocol can be extended to diverse benzylic C(sp 3 )−H bonds and shows excellent functional‐group tolerance. Abstract : Straightforward β‐lactam synthesis : Cu‐catalyzed intramolecular oxidative C(sp 3 )−H amidation for the synthesis of β‐lactams has been developed. This reaction proceeds through an intramolecular Kharasch–Sosnovsky‐type C(sp 3 )−H amidation in the presence of a first‐row transition metal, Cu catalyst, and no DG installation is needed (see scheme).